Incorporating Multicultural Education in the Classroom: Benefits for Global Citizenship - Amal Mohammed Ali Al-Mannai; Hala Essa Al Marzooq; Wafa Jawad Al-Arrayed (International Journal of Educational Research, 2024)
This research examines the benefits of incorporating multicultural education into primary and secondary school curricula. Through a mixedmethods approach, we explore how students' attitudes towards diversity and global citizenship are influenced by exposure to multicultural content. Findings indicate that students who engage with multicultural education are more likely to develop empathy, cultural awareness, and a sense of global responsibility. The study suggests that multicultural education is crucial for preparing students to thrive in a diverse, interconnected world.